Policing the Economy: Hyperinflation, Consumption and the Making of Austerity in Greater Buenos Aires, 1989-1991 - Jennifer Adair (Iberoamericana. América Latina - España - Portugal)
This article examines a period of hyperinflation and food riots that swept Greater Buenos Aires from 1989 to 1991. It is based on an analysis of hundreds of declassified police records compiled by the Intelligence Directorate of the Buenos Aires Provincial Police (Dirección de Inteligencia de la Policía de la Provincia de Buenos Aires, DIPPBA). DIPPBA officers tracked the fluctuating price of basic goods, rising rates of urban poverty, and sporadic outbreaks of supermarket lootings. Albeit crafted with an eye toward surveillance and social control, DIPPBA reports shed light on the survival strategies and consumption patterns that urban residents devised to offset the consequences of hyperinflation. As the challenges of prolonged economic crisis drew police attention to the everyday realms of shopping and the marketplace in new ways, DIPPBA archives from this period offer novel insights into the history of consumption by explicitly linking scarcity and citizens’ inability to access basic goods as a matter of national security.